Pengaruh program wellness terhadap perubahan status gizi dan komposi tubuh pada pegawai rawat inap Rumah Sakit Islam Jakarta Cempaka Putih - Syukriah Usman; Mertien Sa’pang; Maria Tambunan; Nazhif Gifari (Poltekkes Kemenkes Aceh, 2024)
Background: Based on the results of the 2022 Employee Medical Check-Up (MCU) at RSIJCP, there were 219 obese employees, with the highest number of obesity cases coming from the inpatient unit, totaling 46 employees. Obesity can increase the risk of degenerative diseases that can disrupt work productivity. Objective: to measure the effect of the Light Weight Challenge program, which includes nutritional education, low-calorie lunches, and exercise, on changes in nutritional status and body composition among inpatient staff at RSIJCP.Methods: This type of research is a Pre-Experimental Design with a One Group Pretest-Posttest approach. Forty-six employees, 7 men and 39 women, completed the four-week program. The Wellness Program included daily low-calorie diet education provided through a WhatsApp group divided into 7 groups, low-calorie lunches every Monday to Saturday, indoor exercise every Wednesday, and outdoor exercise every Friday. However, before the treatment was administered, a pretest (initial measurement) was conducted to determine the initial condition, and after the treatment, a posttest (final measurement) was conducted to determine the final results.Results: There was a significant decrease in the average body weight before the program (84,5±13,3) and after the program (81,9±13,5), with p=0,000. Similarly, there was a significant decrease in BMI before the program (33,5±4,5) and after the program (32,4±4,7), with p=0,000, and Body Fat before the program (38,3±4,2) and after the program (35,3±4,0), with p=0,000. However, there was no significant change in the average visceral fat before the program (17,3±6,1) and after the program (16,7±6,3), with p=0.350.Conclusion : The